The effect of ARB process on corrosion behavior of nanostructured aluminum alloys in Na2HPO4·12H2O and Zn(NO3)2·6H2O PCMs. (January 2020) - Taherian, Mohammad Mahdi; Yousefpour, Mardali; Borhani, Ehsan
Highlights: Investigation the corrosion behavior of fine-grained Al1100 and Al6061 alloys. The effect of ARB process on localized corrosion on Al1100 and Al6061 alloys. The effect PCM materials on corrosion behavior of Al1100 and Al6061 alloys. Short time immersion test was used to study the corrosion properties of Al1100 and Al6061 alloys In PCMs. Abstract: Phase change materials (PCMs), have high thermal energy storage due to hidden heat. One of the PCMs is hydrate salts. The insufficient long term stability of the storage materials, as containers, are the main concern in the energy storage systems which were investigated in this study. In this order, various common metals (Fine-grained Al1100 and Al6061 alloys by six cycles of accumulative roll bonding (ARB)) process were selected, and their corrosion resistance in contact with two different hydrate salts of (Na2 HPO4 ·12H2 O and Zn(NO3 )2 ·6H2 O) were tested. The immersion test method was utilized. In this way, samples were placed in the test tubes containing molten hydrate salts into a thermo-static water bath in three different periods of six, twelve and eighteen days at the temperature range of 55 to 60 °C. After each period, the sample weight loss rate was measured, and then the corrosion rate was calculated. The corrosion rate of ARBed Al 1100 and ARBed Al 6061 alloys in the Na2 HPO4 ·12H2 O at the end of eighteen days were 103.07 and 78.82 mpy, respectively. Furthermore, the corrosion rate of ARBed Al 1100 and ARBed Al6061 alloys in the Zn(NO3 )2 ·6H2 O was reported 88.67 and 68.71 mpy, respectively. The results indicated that the corrosion rate for Al1100 alloy is less and more than Al6061 alloy in the molten Na2 HPO4 ·12H2 O and molten AZn(NO3 ) 2·6H2 O, respectively.